Counseling on improving public health through herbal honey - Nurillah Fitriyani; Giska Amelia; Amelia Amelia; Berlian Calista; Fadiel Agvasaoka; Elva Angela; Trisna Lestari; Aan Kunaedi (Community Empowerment, 2023)
Gunung Manik is a village with a beautiful environment and well-preserved mountains. Its natural resources yield various abundant commodities, one of which is forest honey. The management of forest honey by farmers in Gunung Manik Village is conducted traditionally, with little attention paid to the preservation of bee colonies, mainly due to the harvesting of bees and their hives. Conversely, farmers' knowledge of the benefits of honey remains limited. This service aims to educate the public about the advantages of honey, promoting a healthier lifestyle through regular consumption. This activity employs a direct and interactive discussion method, incorporating pre-tests and post-tests to gauge participants' comprehension of the presented material. The results of this program indicate that the residents of Gunung Manik Village have gained an understanding of the benefits of honey, leading to increased interest in regular honey consumption and the cultivation of forest honey. These developments are expected to have a positive economic impact on the residents of Gunung Manik Village.